Pharmaceutical care and active treatment in patients with osteochondrosis - Maria Stamova Vakrilova Becheva; Stefka Аchkova Ivanova; Angelina Georgieva Kirkova-Bogdanova (Pensoft Publishers, 2021)
According to the International Classification of Diseases, osteochondrosis is included in the group of diseases of the musculoskeletal system, mainly the spine. The mechanism of the disease is expressed in the disturbance of blood circulation, which nourishes the bone, and hence the damage to bone and cartilage tissue. Objective: This paper aims to present the effect of applied pharmacological and active treatment in 10 patients diagnosed with lumbar osteochondrosis. Methods: We conducted a comprehensive treatment of 10 patients diagnosed with lumbar osteochondrosis without any neurological symptoms during the period 2017-2020. This pharmacological and active treatment lasted from 15 to 17 days. The intensity of the pain symptoms, the general mobility of the spine, and the mobility of the lumbar spine were measured to determine the deficit of the patients. The strength of the flexor and extensor muscles of the body was tested. Results: A decrease in pain intensity, increase in the strength of the abdominal and back muscles and improvement of the mobility of the back muscles were found in all patients after the complex treatment. As a result of the therapy, a reduction in the patient's dysfunctions and the risk of developing disabilities was found. Conclusion: The application of a multidisciplinary approach in patients with osteochondrosis is of great importance for reducing pain intensity and achieving a good functional recovery of motor and stabilizing function of the muscles of the spine.